Relationship between communication satisfaction and organizational identification: a UPM case study - Mustafa Kamal, Daniel Kamal; Hasan, Hamisah; Ahmad, Abdul Mua'ti @ Zamri (2015)
This study examined the relationship between organizational identification and communication satisfaction. Communication satisfaction was represented by seven dimentions: Organizational Perspective, Personal Feedback, Organizational Integration, Supervisory Communication, Horizontal Communication, Media Quality, and Communication Climate .The present study employed a quantitative approach by utilizing a self-administered survey questionnaire. Data was collected using two established instruments, the Downs and Hazen’s Communication Satisfaction Questionnaire (CSQ) and the Mael’s Scale for Organizational Identification (MOI). Random stratified sampling was used and a sample size of 299 respondents consisting of UPM’s academic staff was obtained. Results from this study show that majority of the respondents display a moderate level of Communication Satisfaction within the organization. It also shows that there are weak positive relationships between Organizational Identity and all seven Communication Satisfaction Dimensions. This implies that Communication Satisfaction maybe a questionable antecedent for organizational identification.